MnCO3-RGO composite anode materials: In-situ solvothermal synthesis and electrochemical performances. (10th September 2019) - Zhao, Yan; Mu, Yanlin; Wang, Li; Liu, Mengjiao; Lai, Xin; Bi, Jian; Gao, Daojiang; Chen, Yuanfu
Abstract: The MnCO3 -RGO composite, constructed by MnCO3 microcrystals in-situ nucleated and grown on reduced graphene oxide (RGO) sheets, are synthesized via a facile one-pot solvothermal process. When the MnCO3 -RGO composite is used as anode material, it delivers outstanding electrochemical performance: it exhibits a large capacity of 873 mAh g −1 even after 400 cycles at a current rate of 1 C, which is over 55.6% higher than that of bare MnCO3 (561 mAh g −1 ); most importantly, the MnCO3 -RGO composite demonstrates a superior high-rate performance and long-term stability with a very large capacity of 546 mAh g −1 even after 1000 cycles at a very large current rate of 5 C. This terrific electrochemical performance of MnCO3 -RGO composite is mainly ascribed to its unique architecture: the excellent mechanical flexibility of RGO sheets can stabilize the microstructure of MnCO3 and guarantee the long-term stability during charge/discharge even at large current rate; the high conductivity of RGO sheets can effectively accelerate the transfer of electrons. This work presents a facile and cost-effective synthesis strategy, which gives a guidance for the synthesis of the other transition metal oxides-RGO composite. Graphical abstract: Image 1 Highlights: MnCO3 -RGO network is synthesized by a facile one-pot solvothermal strategy. MnCO3 microcrystals are in-situ nucleated and grown on conductive RGO sheets. MnCO3 -RGO hybrid exhibits outstanding rate capability and superior cyclic stability. Excellent electrochemical performance is due to graphene-based architecture.